Amino-modified hyper-cross-linked polymers with hierarchical porosity for adsorption of salicylic acid from aqueous solution. (April 2019) - Wang, Xiaomei; He, Jielin; Huang, Jianhan
Highlights: Two amino groups modified hyper-cross-linked polymers were synthesized. The introduction of the primary amino groups makes the adsorption enhanced. Acid-base interaction plays a positive role for the adsorption. The maximum adsorption capacities are much larger than most adsorbents. The hierarchical porosity makes the adsorption reach equilibrium more rapidly. Abstract: The synthesis of functionalized hyper-cross-linked polymers (HCLPs) with hierarchical porosity is anticipated for the efficient and rapid adsorption of aromatic compounds from aqueous solution. Herein two amino groups (primary amino and anilino groups) were employed as the functional groups and uploaded on the HCLPs, and hence amino-modified HCLPs were fabricated and their adsorption was comparatively evaluated from aqueous solution using salicylic acid (SA) as the adsorbate. The results reveal that the uploaded amino groups are greatly helpful for the equilibrium adsorption due to the acid-base interaction. In particular, the hierarchical microporous and mesoporous structure is favourable for the kinetic adsorption due to the rapid diffusion of SA in the mesopore channels.